Prognostic impact of minimal extrathyroidal extension in papillary thyroid carcinoma. Issue 52 (December 2016) - Yin, De-Tao; Yu, Kun; Lu, Run-Qing; Li, Xianghua; Xu, Jianhui; Lei, Mengyuan
Abstract : Supplemental Digital Content is available in the text Abstract: Background: It is widely accepted that maximal extrathyroidal extension (ETE) plays a vital role in the prognosis of papillary thyroid carcinoma (PTC). However, there is no consensus among researchers about the meaning of minimal ETE (mETE) in PTC. Herein, we conducted a systematic review and meta-analysis to examine the role of mETE in the prognosis of PTC. Methods: We searched PubMed, EMBASE, and Cochrane search trials databases in English toidentify studies comparing data on disease recurrence in PTC patients with mETE and those with no ETE. To summarize the data related to mETE status, risk ratios and hazard ratios adjusted for potential confounders were used to assess the number of recurrence and time-dependent risks related to mETE status, respectively . Results: According to the inclusion criteria, a total of 7951 patients from 9 studies were included. The recurrence rate in patients with mETE is significantly higher when compared with those with no ETE (risk ratio = 1.70, 95% confidence interval: 1.26–2.28, I 2 = 56%).According to the data summarized with hazard ratios, PTC patients with mETEshowed a significantly increased risk of disease recurrence. Conclusion: mETE is a risk factor for poor prognosis in patients with PTC. Our innovative classification of ETE has its value in assessing the prognosis of PTC.